Teknis Pelaksanaan Pemasangan Struktur Atap Space Frame Truss pada Proyek Pembangunan GGM Majalengka - Muhammad Wafi Hariry; Yayat Hendrayana (Universitas Majalengka, 2024)
The government continues to strive to improve the quality of sports facilities and infrastructure in various cities and districts throughout Indonesia. To realize this effort, the Majalengka Regency government is collaborating with PT. Pertamina (Persero) Tbk. carrying out the reconstruction of the Majalengka Youth Generation Center (GGM). This practical work aims to discuss the technical implementation of installing space frame truss roof structures and discuss the application of structural mechanics in the field of roof construction, especially space frame structures. The author used the interview method with the site engineering manager and the structure method, observation during the installation at the site, reviewing the rules of SNI 1721:2020 and SNI 1729:2020 as well as applicable case studies to prepare this practical work report. Modeling and structural analysis of a typical 13/14 space frame block series using SAP2000 v14 software. The structural analysis results obtained for the space frame structure used steel pipes Ø76.2 mm and Ø63.5 mm; steel pipe thickness, namely 3.2 mm and 2.8 mm; base plate connection measuring 350 x 350 mm with a thickness of 25.00 mm; 8 anchors with a diameter of 16.00 mm, are safe and suitable for use.